2020
DOI: 10.3389/fmicb.2020.01700
|View full text |Cite
|
Sign up to set email alerts
|

Two MarR-Type Repressors Balance Precursor Uptake and Glycine Betaine Synthesis in Bacillus subtilis to Provide Cytoprotection Against Sustained Osmotic Stress

Abstract: Bacillus subtilis adjusts to high osmolarity surroundings through the amassing of compatible solutes. It synthesizes the compatible solute glycine betaine from prior imported choline and scavenges many pre-formed osmostress protectants, including glycine betaine, from environmental sources. Choline is imported through the substrate-restricted ABC transporter OpuB and the closely related, but promiscuous, OpuC system, followed by its GbsAB-mediated oxidation to glycine betaine. We have investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 70 publications
(251 reference statements)
0
6
0
Order By: Relevance
“…The MdtRP operon of Bacillus sp. confers resistance to several antibiotics such as novobiocin, streptomycin and actinomycin, and is regulated by the MarR repressor ( Gupta et al, 2019 ; Warmbold et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MdtRP operon of Bacillus sp. confers resistance to several antibiotics such as novobiocin, streptomycin and actinomycin, and is regulated by the MarR repressor ( Gupta et al, 2019 ; Warmbold et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that transporter proteins play a central role in metabolic and energy-producing pathways in bacteria that respond to osmotic stress [ 34 , 35 ]. We found that the most of the genes differentially regulated by FtcR in biofilm cells encoded transport and binding proteins, suggesting that FtcR mediates the regulation of transport during the development of B. melitensis 16M biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have indicated that the ABC transporters play a central role in metabolic and energy-producing pathways in bacteria that respond to osmotic stress ( Tam and Saier, 1993 ; Warmbold et al, 2020 ). The gene expression changes related to ABC transporter pathways were assessed to explore whether this pathway can respond to osmotic stress in the B. melitensis 16M biofilm.…”
Section: Resultsmentioning
confidence: 99%